Histopathological insights into mitral valve prolapse-induced fibrosis - Dieterlen, Maja-Theresa; Klaeske, Kristin; Spampinato, Ricardo; Marin-Cuartas, Mateo; Wiesner, Karoline; Morningstar, Jordan; Norris, Russell A.; Melnitchouk, Serguei; Levine, Robert A.; van Kampen, Antonia; Borger, Michael A. (Frontiers in Cardiovascular Medicine, 2023)
Mitral valve prolapse (MVP) is a cardiac valve disease that not only affects the mitral valve (MV), provoking mitral regurgitation, but also leads to maladaptive structural changes in the heart. Such structural changes include the formation of left ventricular (LV) regionalized fibrosis, especially affecting the papillary muscles and inferobasal LV wall. The occurrence of regional fibrosis in MVP patients is hypothesized to be a consequence of increased mechanical stress on the papillary muscles and surrounding myocardium during systole and altered mitral annular motion. These mechanisms appear to induce fibrosis in valve-linked regions, independent of volume-overload remodeling effects of mitral regurgitation. In clinical practice, quantification of myocardial fibrosis is performed with cardiovascular magnetic resonance (CMR) imaging, even though CMR has sensitivity limitations in detecting myocardial fibrosis, especially in detecting interstitial fibrosis. Regional LV fibrosis is clinically relevant because even in the absence of mitral regurgitation, it has been associated with ventricular arrhythmias and sudden cardiac death in MVP patients. Myocardial fibrosis may also be associated with LV dysfunction following MV surgery. The current article provides an overview of current histopathological studies investigating LV fibrosis and remodeling in MVP patients. In addition, we elucidate the ability of histopathological studies to quantify fibrotic remodeling in MVP and gain deeper understanding of the pathophysiological processes. Furthermore, molecular changes such as alterations in collagen expression in MVP patients are reviewed.